Framing the Health Workforce Agenda Beyond Economic Growth - Remco van de Pas; Linda Mans; Marielle Bemelmans; Anja Krumeich (Kerman University of Medical Sciences, 2018)
The fourth Global Forum on Human Resources (HRH) for Health was held in Ireland November 2017. Its Dublin declaration mentions that strategic investments in the health workforce could contribute to sustainable and inclusive growth and are an imperative to shared prosperity. What is remarkable about the investment frame for health workforce development is that there is little debate about the type of economic development to be pursued. This article provides three cautionary considerations and argues that, in the longer term, a perspective beyond the dominant economic frame is required to further equitable development of the global health workforce. The first argument includes the notion that the growth that is triggered may not be as inclusive as proponents say it is. Secondly, there are considerable questions on the possibility of expanding fiscal space in low-income countries for public goods such as health services and the sustainability of the resulting economic growth. Thirdly, there is a growing consideration that economic growth solely expressed as increasing gross domestic product (GDP) might have intrinsic problems in advancing sustainable development outcomes. Economic development goals are a useful approach to guiding health workforce policies and health employment but this depends very much on the context. Alternative development models and policy options, such as a Job Guarantee scheme, need to be assessed, deliberated and tested. This would meet considerable political challenges but a narrow single story and frame of economic development is to be rejected.